(untitled) (Fiep Bulletin - online, 2016)
Brazil has a fleet of trucks superior to 2, 2 millions of vehicles. However, the organization of work in this category doesn’t comply with the laws governing the profession. Intense rhythms, no breaks, and pressure in productivity imposes considerable professional wear on your health. The objective of this study was checking the prevalence of cardiovascular risks in long route truckers. This quantitative descriptive study was performed with 96 drivers aged man 22 to 65 years (±10, 10). The cardiovascular risk was evaluated subjectively through the waist and hip relationship (WHR) with reference of classification according to World Health Organization, and analyzed by the Bioestatic 5.3.The results showed 20% low risk,49% moderated risk,28% high risk and 3% with very high risk. We conclude with this study that the evaluated truckers presented one sedentary lifestyle imposed by the inadequate work organization, resulting in a significant percentage of truckers with cardiovascular risks. Thus suggests to this population an improvement in the organization of work as well as periodic monitoring of blood pressure, cholesterol, triglycerides and blood sugar, which should be associated with a better lifestyle and healthy eating.